Приключения Тома Сойера - Твен Марк (Школьная библиотека, 2018)
Экземпляры: ф.6 (20190809) / Инвентарный номер: 3154zzz / Цена: / Сис.шифр: 84(7Сое)-4 / Авт.знак: Т 26 / ГРНТИ: 17.82.93 / ББК: 84(7Сое)-44